2003
DOI: 10.1111/j.1467-8659..00718.x
|View full text |Cite
|
Sign up to set email alerts
|

BRDF Measurement Modelling using Wavelets for Efficient Path Tracing

Abstract: Physically based rendering needs numerical models from real measurements, or analytical models from material definitions, of the Bidirectional Reflectance Distribution Function (BRDF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This example illustrates that the whole radiometric information is useful to perform an accurate physical simulation. We have already shown that a better compression, according to modelling error, can be reached with our approach compared to the work of Lalonde at fixed wavelength [9]. Table 3 also demonstrates that our adaptive generic compression scheme significantly improve spectral modelling at high compression rates compared to the results we have presented in [9].…”
Section: Brdfssupporting
confidence: 55%
See 4 more Smart Citations
“…This example illustrates that the whole radiometric information is useful to perform an accurate physical simulation. We have already shown that a better compression, according to modelling error, can be reached with our approach compared to the work of Lalonde at fixed wavelength [9]. Table 3 also demonstrates that our adaptive generic compression scheme significantly improve spectral modelling at high compression rates compared to the results we have presented in [9].…”
Section: Brdfssupporting
confidence: 55%
“…We have already shown that a better compression, according to modelling error, can be reached with our approach compared to the work of Lalonde at fixed wavelength [9]. Table 3 also demonstrates that our adaptive generic compression scheme significantly improve spectral modelling at high compression rates compared to the results we have presented in [9]. For instance the relative L 2 error has been respectively reduced by 34%, 70%, and 46% for the spectralon, plywood and plastic BRDFs in the case of the 128:1 compression ra- tio.…”
Section: Brdfsmentioning
confidence: 91%
See 3 more Smart Citations